(untitled) (Research, Society and Development, 2022)
This article deals with the contribution of Micro and Small Enterprises (MSEs) in the tax revenues on the Circulation taxation of Goods and Interstate or Intermunicipal Transport and Communication Services (ICMS), as the main means of wealth generation for the States of Brazil. The objective of the research is to analyze the contribution of MSEs opting for Simples Nacional in the collection of ICMS in Brazilian States. Therefore, a descriptive, exploratory and correlational study was carried out, through documentary data, analyzing the period from 2007 to 2011, corresponding to the period of government, respectively, of Lula and Dilma. The results showed that the variables under study are positively and significantly correlated with each other, when the variables are analyzed in isolation, as well as together, highlighting in the Trade Balance the pairing averages between the years 2007 and 2011, as well as in these same years, but with an emphasis on the Southeast region, the study highlighted the differences in values for ICMS collection, number of Simples Nacional and ICMS subscribers collected by this regime. In this way, it was possible to conclude the relevance of companies opting for Simples Nacional and the ICMS collected by them in relation to the collection of ICMS as a whole in Brazilian states.